Periodicals Received (Review of Economic Studies, 1938)
Journal Article Periodicals Received Get access The Review of Economic Studies, Volume 5, Issue 3, June 1938, Page 240, https://doi.org/10.1093/restud/5.3.240 Published: 01 June 1938